Approach to Constructing Symmetric Cryptographic Systems Ensuring Specified Resilience to Cryptoanalysis over the Long-Term Time Horizon - Tarasenko, Sergey; Ivanov, Yuri (Journal of Science and Technology on Information security, 2023)
Abstract— The paper presents the results of an analysis of the decrease in cryptographic strength of the most common symmetric ciphers, taking into account the development of cryptanalytic methods. The vector of the threat to the reduction of information confidentiality stored and processed in information systems in the long term has been determined. An approach to constructing hybrid ciphers, based on the symbiosis of a composite cipher and the Vernam cipher, has been proposed to enhance the asymptotic cryptographic strength of symmetric cryptographic systems used for data encryption in information systems, the relevance of stored and processed information in which does not significantly decrease over time. For instance, this is applicable to information systems built on distributed ledger technology (blockchain networks).